TOLERANSI ANTAR RUMAT BERAGAMA DALAM PERSPEKTIF HADIS - Yenni Rahman (Jurnal Ilmiah Al-Furqan: Al-qur'an Bahasa dan Seni, 2017)
The purpose of the research is to know the basic concept of tolerance among religious people which is based on hadiths. It must be careful in comprehending tolerance among religious people because it can make us blur in interpreting our religion itself. The type of research is library research. The resource of data of the research is classified into two groups; primary and secondary data. The method used in the research is the thematic method called maudhu’i. Maudhu’i method is useful to take the conclusion and comprehensive interpretation. Maudhu’i method collects one topic and purpose related hadiths and the interpretation completed by explanation, expression, and interpretation of the problem. In the discussion on the interpretation of hadiths, it is used textual and contextual hadiths approaches. The Textual interpretation approach is the earliest one used in interpreting the prophet’s hadiths. Meanwhile, the contextual approach is to comprehend the meaning and purpose of the prophet’s hadiths by referring to an analysis of textual hadiths. The second approach is contextual comprehension. The context here means a situation relating to an event of sentences to support the meaning of hadiths.